Associações entre borboletas frugívoras em áreas de floresta com diferentes históricos de perturbação antrópica - Guidelli, Rodrigo Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Em 2009 Uehara Prado et al., coletaram uma grande quantidade de dados para avaliar o papel das borboletas da família Nymphalidae como bioindicadoras, porém esses dados não foram utilizados em sua totalidade. O presente estudo está direcionado à experimentação e modelagem de interações ecológicas, a partir dos dados obtidos por Uehara-Prado et al. (2009), juntamente com aqueles não previamente utilizados que, no intuito de extrair o máximo de informação de relevância biológica e ecológica. Para tanto, foram utilizados três diferentes tipos de abordagens: (1) Biclusterização (Cheng & Church, 2000; Madeira & Oliveira, 2004); (2) Árvores de decisão (Quinlan, 1986; Bell, 1999; De’ath & Fabricius, 2000; Olden et al., 2008) e (3) Redes Bayesianas (Korb & Nicholson, 2003; McCann et al., 2006; Chen & Pollino, 2012; Pearl, 2014). Os resultados se mostraram bastante promissores, e as três ferramentas atingiram as expectativas; em biclusterização, conseguimos identificar todos os padrões de correlação dentro dos cenários apresentados, árvores de decisão se mostraram extremamente eficazes na classificação das variáveis apresentadas e as Redes Bayesianas conseguiram identificar quais variáveis influenciavam ou eram influenciadas pelas outras. Com este trabalho esperamos incentivar outros pesquisadores à revisitarem antigas bases de dados com ferramentas computacionais mais modernas, pois seu potencial é extraordinário.

Elucidating the complex interactions networks in ecological systems is not an easy task (Proulx et al., 2005) and, in order to extract information in an efficient way, powerful computational tools and the right approach, to the types of scenario to be studied, are required. In 2009 UeharaPrado et al., collected a great amount of data to assess the role of the Nymphalidae family of butterflies as bio-indicators, but these data were not used in its entirety. This study is aimed at experimentation and modeling of the ecological interactions from the data obtained by UeharaPrado et al. (2009), along with those not previously used, in order to extract the maximum information of biological and ecological significance. Therefore, three different approaches were used: (1) Biclusterization (Cheng & Church, 2000; Wood& Olive, 2004); (2) Decision Trees (Quinlan, 1986; Bell, 1999; De'ath & Fabricius., 2000; Olden et al, 2008) and (3) Bayesian Networks (Korb & Nicholson, 2003; McCann et al., 2006; Chen & Pollino, 2012; Pearl, 2014). The results were very promising, and the three tools reached our expectations; with Biclusterization we managed to identify all the correlation patterns inside the scenarios presented, Decision Trees proved to be extremely effective in the classification of the variables and the Bayesian Networks were able to identify what variables influenced or were influenced by the others. With this work, we hope to encourage other researchers to revisit old databases with more modern computational tools, because its potential is extraordinary.
Associations between fruit-feeding butterflies in forest areas with different historics of anthropic disturbances
Keywords: Borboletas frugívoras; Biclusterização; Árvores de Decisão; Redes Bayesianas; Fruit-feeding butterflies; Biclustering; Decision trees; Bayesian networks